Clinical Profile and Outcomes of Acute Kidney Injury in Intensive Care Units: A Prospective Single-center Study - Anil Kumar Chetlapalli; Ravindra Attur Prabhu; Ashwija Kolakemar; Indu Ramachandra Rao (Indian Journal of Kidney Diseases)
Background: Acute kidney injury (AKI) is common in critically ill patients and is associated with poor outcomes. We studied the clinical spectrum and outcomes of AKI in patients admitted to intensive care units (ICUs). Methods: This prospective observational cohort study included 763 consecutive patients admitted to the main ICU of a large medical college hospital in Karnataka between January 2019 and March 2019. Demographic and clinical data including primary diagnosis, comorbidities, Sequential Organ Failure Assessment (SOFA), and Acute Physiology and Chronic Health Evaluation-II (APACHE-II) scores at the time of admission were collected. Serum creatinine and blood urea values at admission were recorded and AKI was staged as per KDIGO guidelines. Data on in-hospital outcomes such as mortality and duration of ICU stay and mechanical ventilation were collected. Results: The incidence of AKI was 32.4% (247 out of 763 patients). The mean age of the cohort was 56.1 ± 17.12 years, and 63% were male. Septic acute tubular necrosis (ATN) was the most common cause of AKI (60.7%), followed by toxic ATN (14.6%) and prerenal causes (22.6%). Stage 3 AKI was seen in 48.4%, with (24.2%) requiring dialysis. Mortality was seen in 63.9%. Those with Stage 3 AKI had higher mortality (76.7%), compared to that in Stage 1 (48.7%) and Stage 2 (57.1%) AKI (P < 0.001). Hypotension (odds ratio [OR]: 3.37, 95% confidence interval [CI]: 1.65–6.90, P < 0.001), anemia (OR: 2.13, 95% CI: 1.22–3.71, P = 0.007), and initiation of renal replacement therapy (RRT) (OR: 1.99, 95% CI: 1.03–3.82, P = 0.03) were significantly associated with mortality. The area under the curve (AUC) for SOFA score as a predictor of mortality in those with AKI was 0.83, while the AUC for APACHE-II score was 0.76. Conclusions: AKI occurred in about a third of critically ill patients in our study, with sepsis being the most important cause. Hypotension, anemia, and the need for RRT were significant predictors of mortality. The SOFA score was a better predictor of mortality in those with AKI than the APACHE-II scores.